FACTORS OF INVESTOR BEHAVIOR IN SHARIA STOCK: A THEORY OF PLANNED BEHAVIOR PERSPECTIVE - Priantinah, Denies; Dewanti, Patriani Wahyu; Novitasari, Budi Tiara; Sari, Ratna Candra (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2023)
This study aims to investigate the impact of attitude factors on behavior through investor intentions, subjective norms, behavior, religiosity, religious events, behavioral control, and profit maximization. These factors were analyzed for their influence on investment behavior in Islamic stocks mediated by investor intentions. This research is a type of quantitative research using primary data. The data collection is carried out on respondents with stock accounts for transactions. This research included 42 participants who are investors actively engaged in trading stocks on the Indonesia Stock Exchange and possess a stock account. The selection of investor respondents is expected to reflect accurate decisions in the investment decision-making process. Data was obtained through a research instrument in the form of a questionnaire designed to accommodate the variables to be studied—data analysis using PLS with Structural Equation Analysis (SEM). The results show that subjective norms, religious factors, religious holidays, and profit maximization separately influence investor behavior through investor intentions. Also, this study found that personal criteria do not affect investor intentions, and behavioral control influences investor behavior. This study contributes theoretical implications to augment the literature on investor behavior in Shariah-compliant stocks. Furthermore, it provides practical implications as insights to aid investors in making decisions regarding Sharia-compliant stocks